Pelayanan PAK di Gereja Bagi Anak Sekolah Minggu - Baginda Sitompul; Debora Sitohang; Anrian Simamora; Binsar Simanjuntak (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The study aims to find out what the ideal church service is like for Sunday school children. The research method used is the study of libraries, interview approaches and observation of the ministry of several churches for Sunday schoolchildren. Through a number of literacy, observation and interviews with a number of Sunday school teachers, it is known that the problem of ministry to Sunday school largely arises from the church itself where many weaknesses lie in the Pastor and Assembly who are still less serious about improving the ministry of PAK to children in the church. Some suggestions to address the problem are: 1). Priests should facilitate teaching, provide week school curriculum and actively engage in serving Sunday school worship. 2). The Church needs to include a special budget for the increase in Sunday School Teacher’s HR. 3). The Church needs to periodically evaluate the Sunday school service. 4). The Church needs to work on service facilities ranging from child-friendly specialty spaces. 5). The Church needs to engage members of the congregation who have pedagogic and theological competencies to support Sunday school service. 6). Even in limitations, Sunday school teachers need to update their knowledge and skills in varying the teaching methods of week schoolchildren.